2021
DOI: 10.1097/dad.0000000000001695
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Spectrum of Findings Associated With Tattoos: Multicenter Study Series of 230 Cases

Abstract: Importance: Reactions to tattoo may simulate common dermatosis or skin neoplasms. Histopathology allows diagnosis and helps determining the level and degree of inflammation associated, consequently orientating treatment.Objective: To describe the histological features found in biopsies of cutaneous reactions to tattoo.Design: This study was designed as a multicenter case series.Setting: All consecutive histopathological samples of tattoos referred from 1992 to 2019 to the Hospital General de Catalunya, Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 82 publications
(133 reference statements)
0
13
0
Order By: Relevance
“…A recent retrospective study by Maya et al 2 reviewed 230 tattoo skin specimens and found that common inflammatory patterns associated with tattoos were fibrosing reactions (79/117, 68%), followed by granulomatous reactions (56/117, 48%), lichenoid reactions (33/117, 28%), epithelial hyperplasia (28/117, 24%), pseudolymphoma (27/117, 23%), and spongiotic reactions (27/117, 23%). Combined features of 2 or more types of inflammatory patterns were seen in 64% cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study by Maya et al 2 reviewed 230 tattoo skin specimens and found that common inflammatory patterns associated with tattoos were fibrosing reactions (79/117, 68%), followed by granulomatous reactions (56/117, 48%), lichenoid reactions (33/117, 28%), epithelial hyperplasia (28/117, 24%), pseudolymphoma (27/117, 23%), and spongiotic reactions (27/117, 23%). Combined features of 2 or more types of inflammatory patterns were seen in 64% cases.…”
Section: Discussionmentioning
confidence: 99%
“…Tattoo reactions have become more common because tattoos gain visibility and popularity globally. 1,2 A variety of inflammatory patterns have been described in association with tattoos-including fibrosing, granulomatous, lichenoid, pseudolymphomatous, and spongiotic patterns. 2 Some tattoos have been associated with allergic hypersensitivity reactions, although the presence of eosinophils is not that common.…”
Section: Introductionmentioning
confidence: 99%
“…37 Histologically, tattoo complications are characterized by severe inflammation with a high share of lymphocytes, histiocytes and macrophages. [38][39][40] Most frequently observed patterns were mixed and included fibrosis, interface activity and major signs of type IV reactions like spongiosis and acanthosis. 38,[40][41][42] Severe allergic reactions do usually not respond to medical treatment with corticosteroids and often need complete removal of the colorant from the skin, which can be achieved by surgical or CO 2 -laser removal.…”
Section: Inflammatory Tattoo Reactions and Prevalencementioning
confidence: 99%
“…[38][39][40] Most frequently observed patterns were mixed and included fibrosis, interface activity and major signs of type IV reactions like spongiosis and acanthosis. 38,[40][41][42] Severe allergic reactions do usually not respond to medical treatment with corticosteroids and often need complete removal of the colorant from the skin, which can be achieved by surgical or CO 2 -laser removal. 43,44 In a small German case series, even superficial removal of affected tattoos was sufficient to provide cure and aesthetically acceptable results in three patients.…”
Section: Inflammatory Tattoo Reactions and Prevalencementioning
confidence: 99%
See 1 more Smart Citation